Meningkatkan Kualitas Produk Segar Asal Tanaman untuk Mendukung Agrowisata di Sembalun Bumbung - David Putra Pratama; Ananda Awaliya; Ni Putu Eka Radianti; Nuraini Nuraini; Uswatun Hasanah; LaluAzis Juanda; Muhammad Tryora Inzaghi; Toni Istofan Zikri; Muhammad Sarjan (Unram Journal of Community Service, 2022)
Sembalun Bumbung Village is one of the many villages in Sembalun subdistrict that is very strategically conditioned, both in the fields of agriculture, plantations and animal husbandry. The natural wealth owned by the people of Sembalun Bumbung is also one of them there are tours or ecotourism in it. So in this case, the increase in natural wealth results is the most important part of our Thematic KKN program with the theme Rumah Pangan Lestari. Fresh processed products as a support base in increasing tourism is one of the most important parts to develop the results of natural wealth and tourism, elaboration and collaboration as a basis for increasing Agrotourism in Sembalun District, Sembalun Bumbung Village